2022
DOI: 10.3390/ijerph192416908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Environments of Professional Nursing Practice and Nurses’ Job Satisfaction

Abstract: (1) Background: The repercussions of work environments were widely studied before the pandemic. However, there are still many difficulties to be discovered considering the impact generated by it. Thus, this study aimed to analyse the impact of COVID-19 on nursing practice environments and nurses’ job satisfaction. (2) Methods: A correlational study was conducted in a hospital in northern Portugal, with the participation of 416 registered nurses. Data were collected in June 2021 through questionnaires. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
3
0
9
Order By: Relevance
“…The opposite results are described by various articles in the literature, showing an increase in nurse satisfaction during the COVID-19 pandemic. Thus, a study conducted at a clinical hospital in northern Portugal in 2022 concluded that the general satisfaction of nurses increased statistically significantly during the COVID-19 pandemic compared to the pre-pandemic period [ 29 ]. A high degree of job satisfaction is also present among nurses in Valencia (Spain), with values measured between 29 March and 8 April 2020 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The opposite results are described by various articles in the literature, showing an increase in nurse satisfaction during the COVID-19 pandemic. Thus, a study conducted at a clinical hospital in northern Portugal in 2022 concluded that the general satisfaction of nurses increased statistically significantly during the COVID-19 pandemic compared to the pre-pandemic period [ 29 ]. A high degree of job satisfaction is also present among nurses in Valencia (Spain), with values measured between 29 March and 8 April 2020 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors have not found any research results depicting the job satisfaction of nurses in early 2023. However, job satisfaction among nurses during the first and second years of the pandemic was found to have decreased (Choi et al, 2022 ; Piotrowski et al, 2022 ; Ribeiro et al, 2022 ). This decline in satisfaction is attributed to the conditions of the COVID-19 pandemic, as evidenced by the study of Labrague and de Los Santos ( 2021 ) in the Philippines, which found a significant correlation between nurses’ fear of COVID-19 and decreased job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies conducted in Poland reported decreased job satisfaction among nurses (Piotrowski et al, 2022 ), while in China, job satisfaction levels remained only moderate (Hanum et al, 2023 ). This is further elucidated by a study on Portuguese nurses, which revealed a significant decline in job satisfaction during the pandemic, particularly regarding remuneration, assessment, recognition, and staffing satisfaction (Ribeiro et al, 2022 ). The decrease in job satisfaction is closely related to a desire to quit due to unfavorable pandemic conditions (de Vries et al, 2023 ; Hanum et al, 2023 ; Piotrowski et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
“…Tras analizar los artículos se evidencia una satisfacción laboral media con tendencia alta. 9,10,12,16,17,19,20,[22][23][24][25][26]28 Con un predominio de las enfermeras del sexo femenino y la edad que oscila de los 35 a 40 años. 12-15, 19-24, 26-28 Por lo que una satisfacción laboral media puede tener varias consecuencias que afectan la salud del individuo, el entorno de trabajo, la calidad de la atención y la eficiencia y eficacia de los servicios de salud.…”
Section: La Satisfacción Laboralunclassified
“…Algunos autores hacen referencia que entre los factores o predictores que incrementan la satisfacción laboral se encuentran la autonomía en el trabajo, el cual permite a las enfermeras ejercer su juicio crítico y tomar decisiones, lo que a su vez mejora su autoestima y compromiso. 9,10,12,16,17,[19][20][21][22][23][24][25][26]28 Cuando tienen la libertad de adaptar la atención a las necesidades de los pacientes y contribuir a la mejora continua de su organización, experimentan un mayor sentido de propósito, compromiso y logro en su trabajo. 15,24 La promoción profesional y la capacitación constante, los lugares de trabajo que ofrecen oportunidades de crecimiento profesional, como programas de capacitación y desarrollo, hacen que las enfermeras se sientan valoradas al tener la posibilidad de avanzar en sus carreras.…”
Section: Factores Que Promueven La Satisfacción Laboral Del Profesion...unclassified